3 Implementing a classroom assessment technique to improve student engagement, communication, and performance in an introductory animal science laboratory course. (7th December 2018) - Abrams, A; Nold, R; Gonda, M
Abstract: We hypothesized that the use of classroom assessment techniques would improve final exam grades and promote student engagement, communication, and retention of material among college students. A classroom assessment tool was administered weekly to students in an introductory level animal science laboratory course. Of the six laboratory sections (n = 27 per lab section), three sections were randomly selected to complete assessments at the conclusion of each laboratory period. Based on the assessment responses, feedback was provided at the beginning of the next week's laboratory period to clarify material that students had expressed difficulty understanding. Data were collected on student perception of classroom engagement, communication, and learning abilities through a Likert scale survey administered at the end of the semester. Final exam grades and survey responses from students (n = 161) enrolled in this class were compared to evaluate the effect of assessments on student grades and student's perception of learning. Final exam grades were compared between treatment and control groups using a Students t -test and Likert scale survey questions using a Chi-Squared test. Surveys administered to the lab sections that participated in the assessment activity included additional questions to evaluate assessment effectiveness. No differences ( P > 0.05) between groups were observed for final exam grades or student's confidence of their ability for short or long-term retention of the material. Weekly feedback provided to students based on assessment responses had a greater impact on perceived learning ability ( P = 0.014) and classroom engagement ( P = 0.01) than completing the assessment without this feedback. Utilizing assessment techniques to provide directed feedback may positively impact student engagement and learning in the classroom, although enhanced perceived learning was not associated with final exam grades.